2019
DOI: 10.1186/s12906-019-2653-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics of oxyresveratrol alone and in combination with piperine as a bioenhancer in rats

Abstract: Background Oxyresveratrol is a major bioactive component derived from the heartwood of Artocarpus lacucha . This compound exerts several biological activities, including neuroprotective effects in vitro and in vivo. However, there is limited pharmacokinetic information on this compound, especially its distribution in neuronal tissue and its route of excretion. The aim of this study was to investigate the pharmacokinetic profiles of oxyresveratrol alone and in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…However, the brain distribution of PIC and its metabolites remain unclear although previous studies found that hydroxystilbenes including RES and OXY could penetrate through the bloodbrain barrier. [43][44][45] Moreover, our previous study confirmed that pterostilbene (trans-3,5-dimethoxy-4′-hydroxystilbene), the partially methylated RES displayed very abundant brain exposure. [8] As RHA and ISO also possess methoxy group, they might possess favorable brain distribution as well.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…However, the brain distribution of PIC and its metabolites remain unclear although previous studies found that hydroxystilbenes including RES and OXY could penetrate through the bloodbrain barrier. [43][44][45] Moreover, our previous study confirmed that pterostilbene (trans-3,5-dimethoxy-4′-hydroxystilbene), the partially methylated RES displayed very abundant brain exposure. [8] As RHA and ISO also possess methoxy group, they might possess favorable brain distribution as well.…”
Section: Discussionsupporting
confidence: 66%
“…As a substrate inhibitor of COMT with moderate K i values (<15 µ m ), the concentration for PIC to suppress COMT appears to be achievable in human liver after single oral dosing. However, the brain distribution of PIC and its metabolites remain unclear although previous studies found that hydroxystilbenes including RES and OXY could penetrate through the blood–brain barrier . Moreover, our previous study confirmed that pterostilbene ( trans ‐3,5‐dimethoxy‐4′‐hydroxystilbene), the partially methylated RES displayed very abundant brain exposure .…”
Section: Discussionsupporting
confidence: 60%
“…A study of the effect of piperine on the pharmacokinetic profile of oral ORV was conducted [ 283 ]. The oral availability of ORV was enhanced twofold when given in a combination with piperine.…”
Section: Pharmacokinetic Profilementioning
confidence: 99%
“…As mentioned earlier, a novel approach to improve the pharmacokinetic profile of ORV was studied in rats using piperine as the bioenhancer. The oral bioavailability of ORV was increased twofold when ORV was co-administered with piperine [ 283 ].…”
Section: Delivery Systemsmentioning
confidence: 99%
“…Oxyresveratrol (3,5,2 ,4 -tetrahydroxystilbene) and gnetol (3,5,2 ,6 -tetrahydroxystilbene) are the major bioactive stilbenoids. These compounds are contained in plants such as Artocarpus lacucha Buch.-Ham and Gnetum gnemon, which have been used as folk medicines [1]. They have many pharmacological activities such as anti-oxidant, anti-inflammatory, analgesic, antidiabetic, anti-adipogenesis, anticancer, antileukaemic, and antiviral effects [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%